Effect of Cryopreserved Human Cord Blood Leucoconcentrate on Manifestation of Endogenous Intoxication at Acute Purulent Peritonitis - Goltsev, K. A.; Babinets, O. M.; Kozhina, O. Yu.; Ostankova, L. V.; Goltsev, A. N. (Problems of Cryobiology and Cryomedicine, 2011)
At experimental acute purulent peritonitis in animals the relaparotomy, combined injection of ampicillin and cryopreserved cord lood leucoconcentrate has been shown to provide eradication of blood from microorganisms, manifested reduction of colonization of mall intes-tine and infection of abdominal cavity with pathogenic and opportunistic bacteria, decrease in dystrophic and necrotic rocesses in abdominal cavity.